2006
DOI: 10.7589/0090-3558-42.2.259
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of Avian Cholera in Hope Bay, Antarctica

Abstract: During austral summers 1999-2000 and 2000-01, two outbreaks of avian cholera occurred in the Hope Bay area (63 degrees 24'S, 56 degrees 59'W), located on the tip of the Antarctic Peninsula. Eighty-six dead birds were found: five kelp gulls (Larus dominicanus), 36 skuas (Stercorarius sp.), and 45 Adelie penguins (Pygoscelis adeliae). The carcasses were studied using clinical, pathological, and microbiological criteria. Water samples from ponds where birds were settled and samples from 90 healthy birds also were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 23 publications
1
46
1
1
Order By: Relevance
“…Strains of P. multocida isolated from disease conditions in avian hosts are predominantly capsular type A all over the world Jonas et al, 2001;Davies et al, 2004;Leotta et al, 2006). Our study confirmed this observation: 93.5% of our isolates proved to be capsular type A (Table 3).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Strains of P. multocida isolated from disease conditions in avian hosts are predominantly capsular type A all over the world Jonas et al, 2001;Davies et al, 2004;Leotta et al, 2006). Our study confirmed this observation: 93.5% of our isolates proved to be capsular type A (Table 3).…”
Section: Resultssupporting
confidence: 84%
“…The prevalence rates of subspecies gallicida and septica are diverse in the various avian species. Leotta et al (2006) pointed out that the prevalence rate of subspecies gallicida was higher in wild waterfowls than that of subspecies septica. On the other hand, other authors found that subspecies septica was more frequent in poultry (Snipes et al, 1990) and in feral birds (Korbel et al, 1992) than subspecies gallicida.…”
Section: Resultsmentioning
confidence: 99%
“…P. multocida is a common commensal or opportunistic pathogen found in the upper respiratory tracts of most livestock, domestic, and wild animals (34), including chickens (126)(127)(128)(129)(130)(131), turkeys (132,133), and other wild birds (123,(134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144), cattle and bison (121,(145)(146)(147), swine (34, 148-151), rabbits (152)(153)(154), dogs (41, [155][156][157], cats (domestic house cats as well as large wild cats, such as tigers, leopards, cougars, and lions) (39, 42-46, 49, 157-166), goats (125,139,167,168), chimpanzees (169), marine mammals (seals, sea lions, and walruses) (170), and even komodo dragons (171,172). The manifestation and pathological symptoms associated with Pasteurella infection, or "pasteurellosis," range from asymptomatic or mild chronic upper respiratory inflammation to acute, often fatal, pneumonic and/or disseminated disease.…”
Section: Pasteurella Disease In Animals Pasteurellosis Prevalencementioning
confidence: 99%
“…Avian cholera has affected several species of offshore seabird breeding colonies, including Amsterdam Albatross (Diomedea amsterdamensis) and Yellow-nosed Albatross (Thalassarche chlororhynchos; Weimerskirch 2004), Cape Cormorants (Phalacrocorax capensis; Waller and Underhill 2007), Common Murres (Uria aalgae; Osterblom et al 2004), Adelie Pengins (Pygoscelis adeliae), Skuas (Stercorarius spp. ), Kelp Gulls (Larus dominicanus; Leotta et al 2006), and one Southern Giant Petrel (Macronectes gigantus; Leotta et al 2003). Marine birds are also affected outside the breeding season, but this is infrequent (Christensen et al 1997;Bodenstein et al 2015).…”
Section: Introductionmentioning
confidence: 99%